PENGEMBANGAN MODUL ESP UNTUK MAHASISWA PROGRAM STUDY PENJASKESREK STKIP TAMAN SISWA BIMA - Irawan, Ewan; Khusaini, Fakhri; Anhar, Anhar (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This study aims to develop a valid and practical English teaching module for students majoring in sports. This research method is research and development with 5 stages, namely; 1) Need analysis, 2) Design the module, 3) Experts’ validation, 4) Try out module, and 5) Final product. The instruments used to measure the quality of the developed modules are validation questionnaires for media expert and education expert and practicality questionnaires for students and lecturers with an average score. The results of this study indicate that the module developed is very valid with an average value of 93.02% and from the practical aspect this module is very practical to use by lecturers and students.